THE ROLE OF ESTROGENS AND ESTROGEN RECEPTORS IN MELANOMA DEVELOPMENT AND PROGRESSION - Caruntu, C. (Acta Endocrinol (Buchar), 2016)
Melanoma has a significant mortality and its growing incidence is associated with important social and health care costs. Thus, investigation of the complex mechanisms contributing to emergence and development of melanoma are of real interest both in scientific research and clinical practice. Estrogens play an important role in the emergence and development of certain types of cancer, such as breast cancer, endometrial cancer and ovarian cancer, but their role in development of cutaneous melanoma is still a matter of debate. Various data suggest that increased levels of endogenous estrogens during pregnancy or exposure to exogenous estrogens by use of oral contraceptives (OCs) and hormone replacement therapy (HRT) may have a potential role in melanoma development and progression. Moreover, there were revealed several intracellular pathways which can support the connection between estrogens, estrogen receptors (ER) and melanoma. While ER-β plays an antiproliferative role, ER-α promotes cell growth and cellular atypia. Thus, inhibition of ER-β activity in the skin can increase the risk for development of cutaneous melanoma and spread of metastatic cells. However, despite recent advances in this area, the exact role and clinical implications of estrogens and estrogen receptors in melanoma are still not entirely understood and require further investigations.